Auditoría de gestión y su relación con la optimizaciónde los servicios de la unidad Educativa unidad Popular del cantón Quevedo, año 2012. - Veliz Apolo, Génesis Antonieta (2015)
Research work has as its theme: AUDITORÍA DE GESTIÓN Y SU RELACIÓN CON LA OPTIMIZACIÓN DE LOS SERVICIOS DE LA UNIDAD EDUCATIVA UNIDAD POPULAR DEL CANTÓN QUEVEDO, AÑO 2012. The general was: Run a Performance Audit in said Education Unit at yielded information on the failures to improve the management of the audited entity, it required compliance with specific objectives such as: Analyzing the administrative processes through the application of surveys and interviews to determine their level of compliance, assess the internal control procedures the institution in the administrative area to establish risk levels unmet critical weaknesses, establish management indicators to improve the performance of teachers and administrative and Issue a management audit report to officials of the educational establishment for proper decision making . For the development of this work was necessary to use methods, techniques and procedures that were served to acquire knowledge that will contribute to the work process. Regarding the results is the implementation of audit process is about the development of its five phases: Phase I: Getting and reviewing legislation, Phase II: Evaluation of the internal control system, Phase III: Development of findings, Phase IV: Writing the report, the audit report in the comments, conclusions about the deficiencies in each of the areas examined and the corresponding recommendations to be implemented as corrective actions by the authorities Campus is included, the proposed corrective are of great importance and to be implemented will enable the school to reach a total educational leadership and development to be an institution of quality public education.